Monitoring the agri-food system in Myanmar: The rising costs of diets – September 2024 survey round - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
We assess changes in food prices and diet costs based on large-scale surveys of food vendors (fielded from June 2020 until September 2024) and households (fielded in six periods between 2022 to 2024) across rural and urban areas and in all states/regions of Myanmar. Key Findings  Between July 2023 and September 2024, the cost of a healthy and commonly consumed diet increased by 34 and 35 percent, respectively.  The price of rice – the major staple – was more than twice as high in September 2024 compared to two years prior. Prices rose by 29 percent between July 2023 and September 2024, and by only 7 percent between March and September 2024.  In September 2024, cooking oil prices were 88 percent higher than the previous year, but 15 percent lower than two years prior.  In September 2024, the median prices of most protein-rich foods, except for fish, were at least 50 percent higher compared to two years prior. Over the same two-year period, banana prices doubled.  The highest costs for both common and healthy diets are seen in the conflict-affected states of Rakhine and Kachin, where in September 2024, the costs of the healthy diet was about 65 percent higher than the national average and the costs of the common diet costs was about 40 percent higher.  Compared to average casual wages, the healthy and common diets are least affordable in Kachin, Rakhine and Magway and most affordable in Kayin and Mon.  Between the fourth quarter of 2023 and September 2024, the prices of petrol rose by 90 percent, bar soap and paracetamol by nearly 50 percent, and toothpaste by 160 percent. Recommended Actions  Ensuring food is available at affordable prices is crucial to prevent food security and nutrition issues in the country. Therefore, prioritizing a well-functioning agri-food system should be a key focus for all stakeholders.  The food price situation in Rakhine State is most concerning among all states and regions, and the state should be prioritized – to the extent that this possible – for assistance.